Comparative Study of Plastic Waste Management in ASEAN Countries - Rahmadani Rahmadani; Amin Zaki; Nurul Huda (Journal of Humanities Research Sustainability, 2024)
Background. This research departs from the problem of increasing the volume of plastic waste in ASEAN countries which has a serious impact on the environment and human health. Purpose. The purpose of this study is to understand the differences in approaches and effectiveness of plastic waste management in various ASEAN countries, as well as to explore the factors that affect the success of these management.   Method. This study uses a comparative descriptive method by analyzing secondary data from various reliable sources related to policies, infrastructure, and the level of community participation in plastic waste management in ASEAN countries. Results. The results show that countries with strong government policy support, advanced technology, and high community participation, such as Singapore, tend to be more successful in managing plastic waste. In contrast, countries with limited infrastructure and lack of public awareness face challenges in reducing plastic waste. Conclusion. The conclusion of this study emphasizes the importance of a cross-sectoral collaborative approach and the adoption of innovative technologies to improve the effectiveness of plastic waste management in ASEAN. This research is expected to be a reference for policymakers in ASEAN to design a more holistic and sustainable plastic waste management strategy.